Pricing principles and public interention in domestic markets - Ahmed, Raisuddin (International Food Policy Research Institute, 1988)
Public intervention in foodgrain markets is pervasive in most developing countries. Governments procure foodgrains from farmers, import and export, distribute to consumers, set procurement and distribution prices, strive to maintain floor and ceiling prices in markets, and regulate private trade. In doing so they often alter the structure of incentives in the markets. Current debate on market intervention, however, has resulted in a trend towards liberalization of control and regulation in markets of many countries. An important issue is whether or not undesirable changes in incentives can be minimized through improved operation of public and private markets or whether alternative policies for ensuring higher incentives to producers and lower prices to consumers can be devised through, for example, infrastructural development.